Limnogeology in Brazil's "forgotten wilderness": a synthesis from the large floodplain lakes of the Pantanal - McGlue, Michael M.; Silva, Aguinaldo; Corradini, Fabricio A.; Zani, Hiran; Trees, Mark A.; Ellis, Geoffrey S.; Parolin, Mauro; Swarzenski, Peter W.; Cohen, Andrew S.; Assine, Mario L. [UNESP] (Springer, 2011)
Sediment records from floodplain lakes have a large and commonly untapped potential for inferring wetland response to global change. The Brazilian Pantanal is a vast, seasonally inundated savanna floodplain system controlled by the flood pulse of the Upper Paraguay River. Little is known, however, about how floodplain lakes within the Pantanal act as sedimentary basins, or what influence hydroclimatic variables exert on limnogeological processes. This knowledge gap was addressed through an actualistic analysis of three large, shallow (< 5 m) floodplain lakes in the western Pantanal: Lagoa Gaiva, Lagoa Mandior, and Baia Vermelha. The lakes are dilute (CO(3) (2-) > Si(4+) > Ca(2+)), mildly alkaline, freshwater systems, the chemistries and morphometrics of which evolve with seasonal flooding. Lake sills are bathymetric shoals marked by siliciclastic fans and marsh vegetation. Flows at the sills likely undergo seasonal reversals with the changing stage of the Upper Paraguay River. Deposition in deeper waters, typically encountered in proximity to margin-coincident topography, is dominated by reduced silty-clays with abundant siliceous microfossils and organic matter. Stable isotopes of carbon and nitrogen, plus hydrogen index measured on bulk organic matter, suggest that contributions from algae (including cyanobacteria) and other C(3)-vegetation dominate in these environments. The presence of lotic sponge spicules, together with patterns of terrigenous sand deposition and geochemical indicators of productivity, points to the importance of the flood pulse for sediment and nutrient delivery to the lakes. Flood-pulse plumes, waves and bioturbation likewise affect the continuity of sedimentation. Short-lived radioisotopes indicate rates of 0.11-0.24 cm year(-1) at sites of uninterrupted deposition. A conceptual facies model, developed from insights gained from modern seasonal processes, can be used to predict limnogeological change when the lakes become isolated on the floodplain or during intervals associated with a strengthened flood pulse. Amplification of the seasonal cycle over longer time scales suggests carbonate, sandy lowstand fan and terrestrial organic matter deposition during arid periods, whereas deposition of lotic sponges, mixed aquatic organic matter, and highstand deltas characterizes wet intervals. The results hold substantial value for interpreting paleolimnological records from floodplain lakes linked to large tropical rivers with annual flooding cycles.
Keywords: Pantanal; Limnogeology; Floodplain lakes; Tropical wetlands; Sedimentary organic matter; Freshwater sponges